RETRACTED: Study of the lipid peroxidation products dynamics in the blood and liver of different aged rats in experimentally induced dyslipoproteinemia - Tulaeva Olga; Pavlova Olga; Gulenko Olga; Bukareva Olga; Zhelonkin Nikolai (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 138, 00001 (2024), https://doi.org/10.1051/bioconf/202413800001